Bit Error Rate Performance in CDMA Free Space Optical Links with SIK Receiver under Fog Conditions (MIST International Journal of Science and Technology, 2023)
This article presents a novel analytical method for evaluating fog's impact on Bit Error Rate (BER) in an Optical Code Division Multiple Access (OCDMA) Free Space Optical (FSO) connection. The investigation employs an optical encoder and direct detection receiver employing a balanced photo detector with Sequence Inverse Keying (SIK) to explore fog effects. By scrutinizing multiaccess interference (MAI) current and signal current values at the SIK receiver's output under varied fog conditions, we deduce BER expressions for diverse scenarios. These encompass different fog thickness levels, code lengths, simultaneous users, and system parameters. The results reveal substantial OCDMA degradation due to fog thickness and users. Also, the system incurs a marked power penalty at a specific BER, especially with higher fog and user density. However, we identify a potential solution: increasing code length, effectively mitigating fog-induced performance decline.MIJST, Vol. 11, December 2023 : 81-86DOI: https://doi.org/10.47981/j.mijst.11(02)2023.409(81-86)